Inequalities and healthcare reform in Chile: equity of what?. Issue 9 (29th August 2008) - Burrows, J
Abstract : Chile has achieved great success in terms of growth and development. However, growing inequalities exist in relation to income and health status. The previous Chilean government began to reform the healthcare system with the aim of reducing health inequities. What is meant by "equity" in this context? What is the extent of the equity aimed for? A normative framework is required for public policy-makers to consider ideas about fairness in their decisions about healthcare reform. This paper aims to discuss the main features of the Chilean healthcare reform and their implications for such a normative framework.